Regulatory reform in Brazilian infrastructure: Where do we stand? - Armando Castelar Pinheiro (Institute for Applied Economic Research (ipea), 2015)
The main objectives of regulatory reform and privatization of infrastructure in Brazil were to attract new private investment, increase efficiency and reduce the public debt through the use of privatization revenues. Whereas the evidence suggests that regulatory reform (privatization included) has succeed in fostering productivity growth and improving the fiscal accounts, much less has been accomplished by way of raising investment levels. The telecom sector is apparently the only exception to this rule. What accounts for the failure of privatization and regulatory reform to produce the expected boom in infrastructure investment? Was it an error in diagnosis, faulted implementation or lack of additional supporting reforms? What explains the atypical success observed in telecom? What lessons can be learned from this process and how can these be used to make the necessary corrections so as to produced the needed rise in infrastructure investment? This paper tries to answer these questions, reviewing and analyzing the process of regulatory reform in the main infrastructure sectors. In particular, it examines why has investment failed to expand more significantly. The paper discusses regulatory reform in the telecom, electricity, transportation, and water and sanitation sectors, and makes some recommendations for future action. It concludes that although much has been accomplished in reforming Brazilian infrastructure sectors, at least as much remains to be done
Keywords: 330